Current-induced forces in mesoscopic systems: A scattering-matrix approach - Bode, Niels; Kusminskiy, Silvia Viola; Egger, Reinhold; von Oppen, Felix (Beilstein Journal of Nanotechnology, 2012)
Nanoelectromechanical systems are characterized by an intimate connection between electronic and mechanical degrees of freedom. Due to the nanoscopic scale, current flowing through the system noticeably impacts upons the vibrational dynamics of the device, complementing the effect of the vibrational modes on the electronic dynamics. We employ the scattering-matrix approach to quantum transport in order to develop a unified theory of nanoelectromechanical systems out of equilibrium. For a slow mechanical mode the current can be obtained from the Landauer–Büttiker formula in the strictly adiabatic limit. The leading correction to the adiabatic limit reduces to Brouwer’s formula for the current of a quantum pump in the absence of a bias voltage. The principal results of the present paper are the scattering-matrix expressions for the current-induced forces acting on the mechanical degrees of freedom. These forces control the Langevin dynamics of the mechanical modes. Specifically, we derive expressions for the (typically nonconservative) mean force, for the (possibly negative) damping force, an effective “Lorentz” force that exists even for time-reversal-invariant systems, and the fluctuating Langevin force originating from Nyquist and shot noise of the current flow. We apply our general formalism to several simple models that illustrate the peculiar nature of the current-induced forces. Specifically, we find that in out-of-equilibrium situations the current-induced forces can destabilize the mechanical vibrations and cause limit-cycle dynamics.
Keywords: current-induced forces; electronic transport theory; nanoelectromechanical systems; scattering matrix; S-matrix

Quantum Transport - Nazarov, Y.; Blanter, Y. (Cambridge University Press, 2010)

(untitled) - Landauer, R. (IBM J. Res. Dev., 1957)

(untitled) - Landauer, R. (Philos. Mag., 1970)

(untitled) - Büttiker, M.; Imry, Y.; Landauer, R.; Pinhas, S. (Phys. Rev. B, 1985)

(untitled) - Brouwer, P. W. (Phys. Rev. B, 1998)

(untitled) - Avron, J. E.; Elgart, A.; Graf, G. M.; Sadun, L. (Phys. Rev. Lett., 2001)

(untitled) - Entin-Wohlman, O.; Aharony, A.; Levinson, Y. (Phys. Rev. B, 2002)

(untitled) - Moskalets, M.; Büttiker, M. (Phys. Rev. B, 2005)

(untitled) - Craighead, H. G. (Science, 2000)

(untitled) - Roukes, M. L. (Phys. World, 2001)

(untitled) - Weig, E. M.; Blick, R. H.; Brandes, T.; Kirschbaum, J.; Wegscheider, W.; Bichler, M.; Kotthaus, J. P. (Phys. Rev. Lett., 2004)

(untitled) - LeRoy, B. J.; Lemay, S. G.; Kong, J.; Dekker, C. (Nature, 2004)

(untitled) - Bunch, J. S.; van der Zande, A. M.; Verbridge, S. S.; Frank, I. W.; Tanenbaum, D. M.; Parpia, J. M.; Craighead, H. G.; McEuen, P. L. (Science, 2007)

(untitled) - Krive, I. V.; Palevski, A.; Shekhter, R. I.; Jonson, M. (Low Temp. Phys., 2010)

(untitled) - Galperin, M.; Ratner, M. A.; Nitzan, A. (J. Phys.: Condens. Matter, 2007)

(untitled) - Park, H.; Park, J.; Lim, A. K. L.; Anderson, E. H.; Alivisatos, A. P.; McEuen, P. L. (Nature, 2000)

(untitled) - Eom, K.; Park, H. S.; Yoon, D. S.; Kwon, T. (Phys. Rep., 2011)
(And references therein.)

(untitled) - Naik, A.; Buu, O.; LaHaye, M. D.; Armour, A. D.; Clerk, A. A.; Schwab, K. C.; Blencowe, M. P. (Nature, 2006)

(untitled) - Stettenheim, J.; Thalakulam, M.; Pan, F.; Bal, M.; Ji, Z.; Xue, W.; Pfeiffer, L.; West, K.; Blencowe, M. P.; Rimberg, A. J. (Nature, 2010)

(untitled) - Steele, G. A.; Hüttel, A. K.; Witkamp, B.; Poot, M.; Meerwaldt, H. B.; Kouwenhoven, L. P.; van der Zant, H. S. J. (Science, 2009)

(untitled) - Lassagne, B.; Tarakanov, Y.; Kinaret, J.; Garcia-Sanchez, D.; Bachtold, A. (Science, 2009)

(untitled) - Bode, N.; Viola Kusminskiy, S.; Egger, R.; von Oppen, F. (Phys. Rev. Lett., 2011)

(untitled) - Yu, L. H.; Keane, Z. K.; Ciszek, J. W.; Cheng, L.; Stewart, M. P.; Tour, J. M.; Natelson, D. (Phys. Rev. Lett., 2004)

(untitled) - Sapmaz, S.; Jarillo-Herrero, P.; Blanter, Y. M.; Dekker, C.; van der Zant, H. S. J. (Phys. Rev. Lett., 2006)

(untitled) - Leturcq, R.; Stampfer, C.; Inderbitzin, K.; Durrer, L.; Hierold, C.; Mariani, E.; Schultz, M. G.; von Oppen, F.; Ensslin, K. (Nat. Phys., 2009)

(untitled) - Koch, J.; von Oppen, F. (Phys. Rev. Lett., 2005)

(untitled) - Koch, J.; von Oppen, F.; Andreev, A. V. (Phys. Rev. B, 2006)

(untitled) - Mozyrsky, D.; Hastings, M. B.; Martin, I. (Phys. Rev. B, 2006)

(untitled) - Pistolesi, F.; Blanter, Y. M.; Martin, I. (Phys. Rev. B, 2008)

(untitled) - Lü, J.-T.; Brandbyge, M.; Hedegård, P. (Nano Lett., 2010)

(untitled) - Berry, M. V.; Robbins, J. M. (Proc. R. Soc. London, Ser. A, 1993)

(untitled) - Bennett, S. D.; Maassen, J.; Clerk, A. A. (Phys. Rev. Lett., 2010)
(See also Phys. Rev. Lett. 2011, 106, 199902.)

(untitled) - Bennett, S. D.; Maassen, J.; Clerk, A. A. (Phys. Rev. Lett., 2011)

(untitled) - Kindermann, M.; Beenakker, C. W. J. (Phys. Rev. B, 2002)

(untitled) - Brataas, A.; Tserkovnyak, Y.; Bauer, G. E. W. (Phys. Rev. Lett., 2008)

(untitled) - Weick, G.; Pistolesi, F.; Mariani, E.; von Oppen, F. (Phys. Rev. B, 2010)

(untitled) - Weick, G.; von Oppen, F.; Pistolesi, F. (Phys. Rev. B, 2011)

(untitled) - Weick, G.; Meyer, D. M.-A. (Phys. Rev. B, 2011)

(untitled) - Fedorets, D.; Gorelik, L. Y.; Shekhter, R. I.; Jonson, M. (Europhys. Lett., 2002)

(untitled) - Hussein, R.; Metelmann, A.; Zedler, P.; Brandes, T. (Phys. Rev. B, 2010)

(untitled) - Nocera, A.; Perroni, C. A.; Marigliano Ramaglia, V.; Cataudella, V. (Phys. Rev. B, 2011)

(untitled) - Kamenev, A.; Levchenko, A. (Advances in Physics, 2009)

(untitled) - Jauho, A.-P.; Wingreen, N. S.; Meir, Y. (Phys. Rev. B, 1994)

(untitled) - Moskalets, M.; Büttiker, M. (Phys. Rev. B, 2004)

(untitled) - Aleiner, I.; Brouwer, P.; Glazman, L. (Phys. Rep., 2002)

(untitled) - Vavilov, M. G.; Ambegaokar, V.; Aleiner, I. L. (Phys. Rev. B, 2001)

(untitled) - Arrachea, L.; Moskalets, M. (Phys. Rev. B, 2006)

(untitled) - Dundas, D.; McEniry, E. J.; Todorov, T. N. (Nat. Nanotechnol., 2009)

(untitled) - Todorov, T. N.; Dundas, D.; McEniry, E. J. (Phys. Rev. B, 2010)

(untitled) - Clerk, A. A.; Bennett, S. (New J. Phys., 2005)

(untitled) - Lü, J.-T.; Hedegård, P.; Brandbyge, M. (Phys. Rev. Lett., 2011)

(untitled) - Hyldgaard, P. (Mater. Sci. Eng., C, 2003)

(untitled) - Hanggi, P.; Riseborough, P. (Am. J. Phys., 1983)

(untitled) - Djukic, D.; Thygesen, K. S.; Untiedt, C.; Smit, R. H. M.; Jacobsen, K. W.; van Ruitenbeek, J. M. (Phys. Rev. B, 2005)